Pediatric diaphragmatic hernia induced by a rib osteochondroma - Diederik P.J. Smeeing, MD, PhD; Willemijn M. Klein, MD, PhD; Edwin F. Dierselhuis, MD, PhD; Horst E. Daniels, MD, PhD (Radiology Case Reports, 2024)
Diaphragmatic hernia in children is uncommon, especially when not congenital. We present a case of an 11-year old boy with a diaphragmatic hernia caused by a rib osteochondroma. The osteochondroma was surgically removed and the laceration in the diaphragm was repaired. This case shows the importance of being familiar with acquired diaphragmatic hernia in children, to recognize and prevent possible complications in an early stage.